A systems approach to growing the UK electronics and appliance repair economy - Purkiss, Danielle; Pencheva, Polina; Munro, Beth; Miodownik, Mark (Frontiers in Sustainability, 2024)
The UK has a growing problem in the fast and unsustainable accumulation of Waste Electrical and Electronic Equipment (WEEE and EEE as defined by HM Government, 2023), causing a wide range of negative environmental and social impacts. The UK repair economy, by its nature, is a complex system involving an interplay of legislative (i.e. policy, law, regulation), social (i.e. education, health, wellbeing), economic (i.e. fiscal, business models, supply chains) and environmental aspects (i.e. materials and energy use, greenhouse gas emissions), and stakeholders (i.e. citizens, educators, repair professionals, producers, waste processors, policymakers) at a range of scales (i.e. local, national, and global). Growing a successful UK repair economy can help tackle many negative environmental and social impacts including reducing electronic waste, material consumption, mitigating supply chain risk, and regional inequality. To do this, the needs and interactions of stakeholders at local, national and global level should be supported via coordinated policy and regulation initiatives. This article takes a systems approach to understanding the UK repair economy, identifying key policy and regulatory aspects and opportunities for action and development across global, national, and local contexts to help it grow.1 As defined by French law: 'the use of techniques by which the person in charge of placing a product on the market aims to deliberately reduce its lifespan in order to increase its replacement rate' (translation of article L.422-2 of the Consumer Code)